ON SOFT CONTRA SG âŠ‚âˆ¼-CONTINUOUS AND SOFT CONTRA SG Î²-IRRESOLUTE IN TOPOLOGICAL SPACES - Flora, S. Cicily (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
In this paper, we introduced the new class of soft contra semi generalized-Î²-continuous, soft contra semi generalized-Î²-irresolute functions and discussed the relationship with other soft contra-continuous functions.